Addiction as an Attachment Disorder: White Matter Impairment Is Linked to Increased Negative Affective States in Poly-Drug Use - Unterrainer, Human-Friedrich; Hiebler-Ragger, Michaela; Koschutnig, Karl; Fuchshuber, Jürgen; Tscheschner, Sebastian; Url, Maria; Wagner-Skacel, Jolana; Reininghaus, Eva Z.; Papousek, Ilona; Weiss, Elisabeth M.; Fink, Andreas (Frontiers in Human Neuroscience, 2017)
Substance use disorders (SUD) have been shown to be linked to various neuronal and behavioral impairments. In this study, we investigate whether there is a connection between the integrity of white matter (WM) and attachment styles as well as different affective states including spirituality in a group of patients diagnosed for poly-drug use disorder (PUD) in comparison to non-clinical controls. A total sample of 59 right-handed men, comprising the groups of patients with PUD (n=19), recreational drug-using individuals (RUC; n=20) as well as non-drug using controls were recruited (NUC; n=20). For the behavioral assessment, we applied the Adult Attachment-Scale, the Affective Neuroscience Personality-Scale (short version) and the Multidimensional Inventory for Religious/Spiritual Well-Being. Diffusion Tensor Imaging was used to investigate differences in WM neural connectivity. Analyses revealed decreased Fractional Anisotropy and decreased Mean Diffusivity in PUD patients as compared to RUC and NUC. No differences were found between RUC and NUC. Additional ROI analyses suggested that WM impairment in the superior longitudinal fasciculus (SLF) and the superior corona radiata (SCR) was linked to more insecure attachment as well as to more negative affectivity. No substantial correlation was observed with spirituality. These findings are mainly limited by the cross-sectional design of the study. However, our preliminary results support the idea of addiction as an attachment disorder, both at neuronal and behavioral levels. Further research might be focused on the changes of insecure attachment patterns in SUD treatment and their correlation with changes in the brain.